TELAAH KRITIS PANDANGAN ULAMA DAYAH ACEH UTARA DAN ATURAN KHITENTANG ATURAN PERKAWINAN POLIGAMI - Noval, Yusri (Syariah: Jurnal Hukum dan Pemikiran, 2016)
The issue of polygamy is a hot issue that to be debated continuesly. One side polygamy is claimed as exploitation and hegemony of male to female. On the other hand, polygamy is seen have normative reference and it considered as one of the solutions to solve the problems of in infidelity and prostitution. The Indonesian government has been reform the rules of polygamy. In KHI, although it adheres to the principle of monogamy, but the government is still open opportunity for polygamy. However, this rule of KHI is critized bythe dayah scholars of North Aceh. The overview of Ulama dayah is that polygamy rules made by the government out of the Shariâa corridors. Also that issueto be politicied and adopt the rules of the west to complicate polygamy practise and legalized prostitution. Therefor, this study aim to examine and analyze the rules of KHI regarding polygamy from sharia aspect, social, cultural, welfare and others. Also, analyze and critize the views and thoughts of dayah scholar about the rules of polygamy in KHI.